Is Omentectomy Mandatory Among Early Stage (I, II) Malignant Ovarian Germ Cell Tumor Patients? A Retrospective Study of 223 Cases. Issue 7 (September 2017) - Xu, Wenyan; Li, Yanfang
Abstract : Objective: The aim of the study was to investigate whether omentectomy (OMT) is necessary in the operation for apparently early stage malignant ovarian germ cell tumors (MOGCTs). Methods and Materials: Searching medical records database of Sun Yat-sen University Cancer Center from January 1, 1966, to November 30, 2015, patients with MOGCTs were identified and their age, year of diagnosis, tumor grade, histologic subtype, International Federation of Gynecology and Obstetrics stage, nodal findings, gross observation of omentum, and performance of OMT were assessed. Overall survivals of patients with or without OMT were compared using Kaplan-Meier survival curves. Results: A total of 223 MOGCT cases with clinically early stage (stage I and II) disease and with the 3 common histological subtypes of MOGCT were obtained, which include yolk sac tumor (YST), dysgerminoma (DSG), and immature teratoma (IMT). There were 192 stage I cases and 31 stage II cases. Fifty-four patients were diagnosed with YST, 61 with DSG, and 108 with IMT. Omentectomy was performed as part of the initial surgery in 74.0% patients (165/223) and was omitted in 26.0% patients (58/223). Chemotherapy was administered in 88.3% (197/223) of all patients. The median follow-up was 82.0 months. The 10-year overall survival rates of the patients with and without OMT were 90.5% and 98.1%, respectively ( P = 0.156). Regarding different stages or histological subtypes, the 10-year survival rates of the 2 groups were 92.0% versus 97.9% ( P = 0.324, stage I), 83.2% versus 100% ( P = 0.351, stage II), 89.2% versus 100% ( P = 0.303, YST), 94.1% versus 100% ( P = 0.470, DSG), and 89.4% versus 96.0% ( P = 0.405, IMT), respectively. Conclusions: In conclusion, OMT in patients with clinically early stage MOGCT may not improve patient survival and may be omitted.